Quantum chemical study of the photolysis mechanisms of sulfachloropyridazine and the influence of selected divalent metal ions. (November 2015) - Shah, Shaheen; Zhang, Heming; Song, Xuedan; Hao, Ce
Highlights: Sulfur dioxide extrusion product confirmed by two paths in photolysis of SCP. Step 2 of Path-II, estimated as RDS for triplet-sensitized photolysis of SCP. Cu 2+ and Ca 2+ promoted the triplet-sensitized Photolysis of SCP but Zn 2+ inhibits. Increase ASD and ΔNBO of N1–C5 decrease Ea of RDS. Abstract: Sulfonamides have been found in aquatic environments. Degradation of sulfachloropyridazine (SCP) mainly proceeds through direct and indirect photolysis in the aquatic environment. However, the mechanisms underlying the triplet photolysis of SCP and the influence of metal ions on the photolysis mechanism have not yet been fully explained. In this study, we elucidated the triplet photolysis mechanisms of SCP and the effects of three selected metal ions (Zn 2+, Ca 2+, and Cu 2+ ) on the SCP photolysis mechanisms using quantum chemical calculation. Optimization of molecular structures and reaction pathways analysis of SCP were carried out at the B3LYP/6-31+G(d, p) level of theory. Two minimum energy pathways were investigated in the triplet photolysis of SCP. In Step 2 of Path-I, the photolysis product of SCP is a sulfur dioxide extrusion product, (4-(3-chloro-6-iminopyridazine-1(6H)-yl)aniline). The estimated activation energies of Step 2 and Step 3 of Path-I were much higher than in Path-II. Therefore, Path-II was found as the lowest energy pathway to obtain the SCP photoproducts, and Step 2 of Path-II was confirmed as the rate-determining step (RDS) in the photolysis mechanism of SCP. For the RDS of Path-II, computations with the three metal ions complexes (IM1–Cu 2+, IM1–Ca 2+, and IM1–Zn 2+ ) show that the metal ions Cu 2+ and Ca 2+ promote triplet-sensitized photolysis of SCP by reducing the activation energy of RDS of Path-II, whereas Zn 2+ showed an inhibitory effect in photolysis of SCP by increasing the activation energy.